Analisis Mekanisme Pemungutan dan Penyetoran Retribusi Parkir di UPT Kepanjen - Mutoharotur Romadhoni; Aviva Nur Aviani; RM Mahrus Alie (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze the mechanism for collecting and depositing parking fees at UPT Kepanjen. This research uses a qualitative approach with descriptive methods to provide an in-depth picture of the process of collecting and depositing parking fees. Data was obtained through interviews, observation and documentation involving various related parties, such as parking officers, UPT managers and parking service users. The research results show that the mechanism for collecting parking fees at UPT Kepanjen still faces several obstacles, such as a lack of transparency, a recording system that is not yet integrated, and minimal supervision. Apart from that, retribution payments also require improvements in terms of efficiency and accountability. This research recommends several improvements, including the application of information technology for recording and monitoring systems, increased training for parking officers, as well as stricter enforcement of rules to ensure parking fees are deposited on time and in accordance with established procedures. In this way, it is hoped that the mechanism for collecting and depositing parking fees at UPT Kepanjen can run more effectively and transparently, and provide an optimal contribution to regional income.